Factors Related to HIV AIDS Fund Expenditure 2010-2018 (NASA 2019 Data Analysis) - Lely Wahyuniar; Fatien Hamamah; Dheni Fidiyahfi; Leonita Agustine (Faculty of Public Health, Hasanuddin University, Makassar, 2021)
The prevalence rate of HIV/AIDS and various achievement targets are still challenges in HIV/AIDS intervention in Indonesia. Indonesia is required to map out the current resources and their allocation in dealing with HIV AIDS. The objective of this study is to know the distribution and the factors that related with the HIV/AIDS expenditure in the year 2010-2018. This study uses a correlation study design derived from the 2019 National AIDS Spending Assesment (NASA) report and other data sources. The results of the study show that the total expenditure on HIV/AIDS programs in 2017 was 143,053,754 USD and decreased to 107,680,959 USD in 2018. Of the total expenditure, about 60% each came from public funding, an increase of 30% over 10 years. There is a strong relationship between HIV expenditure and the variables of reported HIV cases, ARV coverage, GDP growth and health budget. Total domestic expenditure on HIV and the total health budget had the strongest relationship (R=0.885) with a contribution of 78.3% effect on the health budget (p=0.001). The availability of domestic funds is still limited and is dominated by the allocation of treatment. The high level of dependence on international funding especially on prevention means that the architecture of HIV/AIDS funding needs to be reorganized to protect the sustainability of HIV funding.